Biodiversity and rarity distributions of native freshwater fish in an agricultural landscape: the importance of β diversity between and within water‐body types. Issue 3 (24th September 2015) - Ishiyama, Nobuo; Sueyoshi, Masanao; Watanabe, Nozomi; Nakamura, Futoshi
Abstract: Farmland expansion is a growing threat to aquatic biodiversity. Identifying conservation priority areas in agricultural landscapes is a key issue in freshwater ecology and information on the spatial variability of aquatic biodiversity is vital for prioritization. This study examined patterns of farmland fish assemblages across various water‐body types in northern Japan to develop an effective management plan for freshwater fishes. Water bodies were classified into five types: small lowland streams, small upland streams, large rivers, man‐made ditches, and wetland ponds, and native fishes were collected from each type. The contribution of fish diversity between water‐body types (β2) to the regional fish diversity (γ) was investigated through additive diversity partitioning. Within each water‐body type, the contributions of between‐site diversity (β1) and within‐site diversity (α1) were also examined. The assemblage composition, species richness, and rarity were compared among the water‐body types. The assemblage composition differed significantly among most of the water‐body types, which indicated that the landscape classification was appropriate for representing spatial variations in fish diversity. Additive diversity partitioning revealed that the contributions of β1 and β2 to γ fish diversity were relatively high at 38.2% and 37.3%, respectively, followed by a 24.5% contribution of α1 diversity. This finding demonstrates that the best strategy for conserving regional farmland fish diversity is to preferentially select areas containing various water‐body types as a conservation unit. Among the water‐body types, ditches and streams exhibited the higher contribution ratio for β1 diversity, whereas the contribution of β1 diversity was lower in wetland ponds. The differences in the contribution of β1 diversity might be attributed to human‐induced factors, such as habitat fragmentation or shrinking. These results emphasize that further studies are needed to clarify the factors influencing the β1 diversity of farmland fish to develop better management strategies for each water‐body type. Copyright © 2015 John Wiley & Sons, Ltd.